Importance of physical qualities for speed and change of direction ability in elite female soccer players - Emmonds, S.; Nicholson, G.; Beggs, C.; Jones, B.; Bissas, A. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to determine the importance of physical qualities for speed and change of direction (CoD) ability in female soccer players. Data were collected on 10 female soccer players who were part of a professional English Women's Super League team. Player assessments included anthropometric (stature and body mass), body composition (dual-energy X-ray absorptiometry), speed (10-m and 20-m sprints), CoD ability (505 agility), aerobic (Yo-Yo Intermittent Recovery Test), lower-body strength (bilateral knee extensions), and power (countermovement jump [CMJ], squat jump [SJ], 30-cm drop jump [DJ]) measures. The relationships between the variables were evaluated using eigenvector analysis and Pearson correlation analysis. Multiple linear regression revealed that the performance variables (10 and 20 m speed, mean 505, and CoD deficit mean) can be predicted with almost 100% accuracy (i.e., adjusted R2 > 0.999) using various combinations of the predictor variables (DJ height, CMJ height, SJ height, and lean body mass). An increase of 1 SD in DJ height was associated with reductions of -5.636 and -9.082 SD in 10-m and 20-m sprint times. One SD increase in CMJ also results in a reduction of -3.317 and -0.922 SD, respectively, in mean 505 and CoD deficit mean values. This study provides comparative data for professional English female soccer players that can be used by strength and conditioning coaches when monitoring player development and assessing the effectiveness of training programs. Findings highlight the importance of developing reactive strength to improve speed and CoD ability in female soccer players.